Antenatal Depression and Associated Factors among Pregnant Women Attending Antenatal Care Service in Kochi Health Center, Jimma Town, Ethiopia - Yonas Tesfaye; Liyew Agenagnew (Journal of Pregnancy)
Background. Antenatal depression has immense public health importance, as it can adversely affect both the mother and child health. The problem contributes to the disease burden in both developed and developing countries. Despite this, it is less investigated and not getting the necessary attention in the study setting. Objective. The aim of the study was to assess the prevalence of antenatal depression and associated factors among women attending antenatal care (ANC) service in Kochi Health Center, Jimma town, southwest Ethiopia, 2019. Method. Institutional based cross-sectional survey was conducted on 314 pregnant women attending Kochi Health Center from February 15 to April 15, 2019. A systematic random sampling technique was used to include the study participants. Antenatal depression was assessed using the Patient Health Questionnaire (PHQ-9) tool. Data was collected through face-to-face interviews using a pretested and structured questionnaire. Descriptive statistics was done to summarize the dependent and independent variables. Moreover, the chi-square test analysis was done to determine the association between the outcome and explanatory variables. Results. A total of 314 pregnant women participated in the study, making a response rate of 96.7%. The study has revealed a total of 52 (16.6%) of the respondent had antenatal depression. A chi-square test of independence analysis showed a significant association between antenatal depression and marital status, family history of depression, pregnancy planning, history of abortion, social support, and intimate partner violence (P<0.00001). Conclusion. The study has shown that the prevalence of antenatal depression was high and associated with multiple psychosocial, clinical, and obstetric factors. Therefore, screening pregnant women for depression and the provision of necessary mental health services is recommended to mitigate the adverse health outcome of the problem.